The Centrality of Language in Health Communication - Daniele, Franca (European Scientific Journal, ESJ, 2021)
Medical communication and health communication are two close relatives in the field of communication, where medical communication is the mother and health communication is the offspring. Medical communication engages the delivery of scientific, medical, pharmaceutical and biotechnological information and data to health professionals like doctors, pharmacists, nurses, etc. The information includes updates on the latest discoveries provided by the international scientific community. Therefore, the source of this type of communication is represented by medical and scientific publications reporting data generated from basic science and clinical research. Health communications are targeted toward the general public, where the source is represented by health communicators and journalists. In health communications, information is the result of some kind of intra-language translation that allows transformation of the original medical language into a common language. Therefore, health communication derives from rewritings of a complex medical language that cannot always be modified and acquainted to serve the general public. The aim of the present work was to evaluate, in medical communications, the linguistic elements that represent the hard core for the general public. Thus, a qualitative evaluation was carried out on medical abstracts assessing medical terminology and compound phrases. The results of this investigation point out that these two linguistic traits of medical language are especially difficult for the general public due to their particular specialized nature.